SAT0436 Platelet-Rich Plasma versus Hyaluronic Acid in Treatment of Knee Osteoarthitis. (15th July 2016) - El Deeb, A.E.; Khallaf, H.; El Gazzar, N.; El morsy, S.; Hashem, H.
Abstract : Background: Platelet rich plasma (PRP) therapy is a simple, low-cost and minimally invasive method that provides a natural concentrate of autologous blood growth factors (GFs) that can be used to enhance tissue regeneration (1). Recent evidences have shown that PRP can be helpful as an osteoarthritis (OA) therapeutic tool by intra-articular injection (2). Hyaluronic acid (HA)is widely used therapy for relief of OA pain and stiffness by intraarticular injection. In addition, there is a sufficient evidence for being significant disease-modifying effects (3, 4). Objectives: our aim was to compare the clinical efficacy of platelet-rich plasma with that of hyaluronic acid viscosupplementation. Methods: This study included forty patients with knee osteoarthritis. These patients were selected from the outpatient clinic of Physical Medicine, Rheumatology and Rehabilitation Department, Faculty of Medicine, Tanta University. Patients were randomly divided into two groups. The first group consisted of 20 patients treated by using intraarticular injection of 2 ml autologous PRP (PRP group).The second group consisted of 20 patients they were treated by using intraarticular injections of low molecular weight (hyaluronic acid [HA]) (32mg/2mL) of HA (HA group). All patients received 3 injections with one week interval (3) For Follow up: The subjective clinical outcome were measured at baseline, 1, 3, 6 and 12 months after the last treatment dose using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and the 11-point pain intensity Numeric Rating Scale (NRS) (5). Results: At 1, 3 months' follow-up, the PRP and LW HA groups showed an improvement, with non-significant difference between the two groups. However after 6 months follow up there was significant improvement in PRP group than HA group (P<0.005). The follow up after 12 months reveled subsided improvement than that was at 6 months. Nevertheless, this subsidence was less in PRP group. Conclusions: Autologous PRP injections showed more and longer efficacy than HA injections in reducing pain and symptoms and recovering articular function. Further studies are needed to confirm these results and to investigate the persistence of the beneficial effects observed. References: Wasterlain A, Braun HJ and Dragoo JL (2012): Contents and Formulations of Platelet-Rich Plasma. Oper Tech Orthop. 22(1): 33–42. Arnoczky S, Delos D and Rodeo S (2011): What Is Platelet-Rich Plasma? Oper Tech Sports Med. 19(3): 142–8. Cerza F, Carnì S, Carcangiu A, et al (2012): Comparison Between Hyaluronic Acid and Platelet-Rich Plasma, Intra-articular Infiltration in the Treatment of Gonarthrosis. Am J Sports Med. 40(12): 2822–7. Filardo G, Kon E, Di Martino A, et al (2012): Platelet-rich plasma versus hyaluronic acid to treat knee degenerative pathology: study design and preliminary results of a randomized controlled trial. BMC Musculoskelet Disord 2012; 13(1): 229. Altman R, and Bloch (1986): Criteria for the classification and reporting of osteoarthritis of the knee joint. Diagnostic and Therapeutic Criteria Committee. Classification Committee of the American Rheumatism Association. Arthritis Rheum. 29:1039–49. Acknowledgement: Thanks to ALLAH Disclosure of Interest: None declared